Math, asked by monjyotiboro, 3 months ago

in the mean value theorem{ f(b) -f(a) }/b-a=f'c if a=0, b=1/2 and f(x) =x(x-1) (x-2) , find the value of c?
Help me​

Attachments:

Answers

Answered by mathdude500
3

\large\underline{\sf{Solution-}}

Given that

\rm :\longmapsto\:f(x) = x(x - 1)(x - 2) \:  \: on \:  \: [0,  \: \dfrac{1}{2}  \bigg]

Step :- 1

\rm :\longmapsto\:f(x) \: is \: polynomial \:

\bf\implies\:f(x) \: is \:continuous\: on \: [0, \dfrac{1}{2} \bigg]

Step :- 2

\rm :\longmapsto\:f(x) = x(x - 1)(x - 2)

\rm :\longmapsto\:f(x) = x( {x}^{2} - 2x - x + 2)

\rm :\longmapsto\:f(x) = x( {x}^{2} - 3x+ 2)

\rm :\longmapsto\:f(x) = {x}^{3} - 3 {x}^{2} + 2x

On differentiating both sides, w. r. t. x, we get

\rm :\longmapsto\:f'(x) = 3{x}^{2} - 6{x} + 2

\rm :\longmapsto\:f'(x) \: is \: polynomial \:

\bf\implies\:f(x) \: is \:differentiable\: on \: (0, \dfrac{1}{2} \bigg)

Hence, Mean Value Theorem is applicable.

Now,

\rm :\longmapsto\:f(x) = x(x - 1)(x - 2) \:

So,

\rm :\longmapsto\:f(0) = 0

and

\rm :\longmapsto\:f(\dfrac{1}{2} ) = \dfrac{1}{2} (\dfrac{1}{2}  - 1)(\dfrac{1}{2}  - 2) \:

\rm :\longmapsto\:f(\dfrac{1}{2} ) = \dfrac{1}{2} ( - \dfrac{1}{2})( - \dfrac{3}{2}) \:

\rm :\longmapsto\:f(\dfrac{1}{2} ) = \dfrac{3}{8}

Now, Mean Value Theorem is applicable. So, there exist atleast one real number c belongs to (0, 1/2) such that

\rm :\longmapsto\:f'(c) = \dfrac{f(b) - f(a)}{b - a}

\rm :\longmapsto\: {3c}^{2} - 6c + 2 = \dfrac{\dfrac{3}{8}  - 0}{\dfrac{1}{2}  - 0}

\rm :\longmapsto\: {3c}^{2} - 6c + 2 = \dfrac{3}{4}

\rm :\longmapsto\: {12c}^{2} - 24c + 8 = 3

\rm :\longmapsto\: {12c}^{2} - 24c +5 = 0

Now, to get the value of 'c', we have to use Quadratic Formula,

\rm :\longmapsto\:c = \dfrac{ - ( - 24) \:  \pm \:  \sqrt{ {( - 24)}^{2}  - 4 \times 12 \times 5} }{2 \times 12}

\rm :\longmapsto\:c = \dfrac{24\:  \pm \:  \sqrt{576 - 240 }}{24}

\rm :\longmapsto\:c = \dfrac{24\:  \pm \:  \sqrt{336 }}{24}

\rm :\longmapsto\:c = \dfrac{24\:  \pm \:  4\sqrt{21 }}{24}

\rm :\longmapsto\:c = 1 \:  \pm \: \dfrac{ \:  \sqrt{21 }}{6}

\rm :\longmapsto\:c = 1 \:  -  \: \dfrac{ \:  \sqrt{21 }}{6}  \: as \: c \in \: (0, \dfrac{1}{2} \bigg)

Hence,

  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \underbrace{ \boxed{ \bf{ \: Option \: (c) \: is \: correct}}}

Similar questions